High performance SERS platforms via parametric optimization of laser-assisted photodeposition of silver and gold nanoparticles - Hoffmann, Manuel; Wackerow, Stefan; Abdolvand, Amin; Zolotovskaya, Svetlana (University of Dundee, 2021)
Parametric optimization of laser-assisted photocatalytic growth of Ag and Au nanoparticles for high SERS enhancement factor performance informed by design of experiment is demonstrated. The photodeposition process was divided into two phases – seeding and growth – in order to achieve the highest possible nanoparticle surface coverage for the size range from 10 to 100 nm. Substantial difference in the parameter effects between the Ag and Au seeding and growth was found. SERS performance of the photodeposited Ag and Au nanostructures was evaluated at 532, 633 and 785 nm with thiophenol as a probe molecule. A high-enhancement broadband SERS operation was attained with Ag nanostructure grown at high laser fluences. The SERS enhancement factors of 10 to the power of 5 were achieved with both Ag and Au nanostructures.